2014
DOI: 10.1063/1.4900748
|View full text |Cite
|
Sign up to set email alerts
|

Study of gas-puff Z-pinches on COBRA

Abstract: Gas-puff Z-pinch experiments were conducted on the 1 MA, 200 ns pulse duration Cornell Beam Research Accelerator (COBRA) pulsed power generator in order to achieve an understanding of the dynamics and instability development in the imploding and stagnating plasma. The triplenozzle gas-puff valve, pre-ionizer, and load hardware are described. Specific diagnostics for the gas-puff experiments, including a Planar Laser Induced Fluorescence system for measuring the radial neutral density profiles along with a Lase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 44 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…In this case, the current stays in the shell or switch to the rod. Experiments using a Ne-on-Ar gas-puff Z -pinch [27] showed that the pinch column is much tighter when an aluminum wire is placed on axis (see [27,Fig. 21]) compared with the case without wire [27, Fig.…”
Section: Gas Z -Pinch Closing Switchmentioning
confidence: 99%
“…In this case, the current stays in the shell or switch to the rod. Experiments using a Ne-on-Ar gas-puff Z -pinch [27] showed that the pinch column is much tighter when an aluminum wire is placed on axis (see [27,Fig. 21]) compared with the case without wire [27, Fig.…”
Section: Gas Z -Pinch Closing Switchmentioning
confidence: 99%
“…If the driver has a sizable prepulse, then the prepulse may be able to produce enough ionization through the gas before the main pulse arrives. Alternatively, an external system can be used to preionize the gas before the driver pulse; several methods have been reported in the literature, including the use of microwaves [55], electron beams [56], or UV irradiation [57,58]. A uniform initial ionization is thought to improve the reproducibility and symmetry of the pinch [52].…”
Section: B Gas Puff Z Pinchmentioning
confidence: 99%
“…Because of zippering and MRT instability growth, the plasma column disrupts first near the cathode electrode, coincident in time with the K-shell x-ray emission peak (Ti-filtered photodiode). Mitigation of MRT instability growth has received significant attention in the literature, and several techniques have been investigated to reduce the impact of MRT instability on Z pinches, including sheared flow [65], field-line tension via addition of an external axial magnetic field B z [66,67], and tailored or multishell density profiles [58,[68][69][70].…”
Section: B Gas Puff Z Pinchmentioning
confidence: 99%